The opiate receptors - Pasternak, Gavril W.; SpringerLink (Online service). (Totowa, NJ Humana Press Imprint: Humana Press, 2011)
In 1988, Gavril W. Pasternak published the first edition of this seminal text. It was a lucid account of the latest knowledge on opiate receptors and related receptor subtypes, a then controversial field, providing an integrated approach correlating the biochemical, physiological, and pharmacological aspects of opiate reaction. Fully revised and expanded, The Opiate Receptors, 2nd edition presents all the advances made in the field in the past twenty years. It covers a wide variety of topics including, but not limited to, the following: pharmacology of opioid drugs; endogenous opioids; molecular biology of mu receptors; molecular biology of delta receptors; kappa opioid receptor gene and the regulatory mechanisms of its protein expression; opioid receptor signal transduction mechanisms; mu opioid receptor mediated analgesia and reward; kappa opioid receptor function; delta opioid receptor function; genetics of opioid receptor functions in mice; opioid receptor trafficking; opioid receptor dimerization; molecular modulation of in vivo tolerance; and genetics of opioid actions. Written by leading international researchers in the field, this new edition is as groundbreaking and vital as its predecessor.
You?ve Come a Long Way Baby -- The evolution of concepts of opioid receptors -- Pharmacology of opioid drugs -- Opioid receptors: the early years -- Endogenous opioids -- Molecular biology of mu opioid receptors -- Delta Opioid Receptors -- Kappa opioid receptor gene and the regulatory mechanisms of its protein expression -- Opioid receptor signal transduction mechanisms -- Mu opioid receptor mediated analgesia and reward -- Kappa opioid receptor function -- Delta opioid receptor function -- Genetics of opioid receptor functions in mice -- Opioid receptor trafficking -- Opioid receptor dimerization -- Molecular modulation of in vivo tolerance -- Genetics of opioid actions.
Electronic reproduction.
Keywords: Endorphins--Receptors.; Opioids--Receptors.; Electronic books